The Organizational Commitment, Motivation, and Culture on Performance: Job Satisfaction as Mediator at Tiumang Health Center - Kiki Mirella; Elvis Wandi; Jhon Veri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This thesis examines the mediating role of job satisfaction on the effect of organizational commitment, work motivation, and organizational culture on employee performance, addressing the need to optimize human resource outcomes within the healthcare sector. Methods: An explanatory quantitative approach was applied in this study. Conducted at the Tiumang District Health Center, primary data was gathered using Likert-scale questionnaires. A total population sampling technique was utilized, involving 74 medical and administrative staff members. To test the direct and indirect hypotheses, data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM). Results: The findings indicate that organizational commitment, motivation, and work culture have a positive and significant direct impact on both job satisfaction and employee performance. Furthermore, the path analysis confirms that job satisfaction serves as a valid intervening variable, effectively bridging the three independent variables to drive higher overall performance. Implications: Practically, the health center management should prioritize fostering an adaptive work culture and sustaining psychological motivation to maintain high job satisfaction, which ultimately leads to better public healthcare services. Future studies are encouraged to expand the model by incorporating transformational leadership or workload variables across multiple healthcare centers to broaden the generalizability.